IMPACT OF GOOD CORPORATE GOVERNANCE AND SUSTAINABILITY DISCLOSURE ON BANKINGS’ FIRM VALUE LISTED IN BEI - Wijaya, Errin Yani; ', Julya; ', Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of the study is to measure the effect of Good Corporate Governance (GCG) and Sustainability Disclosures on Firm Value. In this study, there are 22 companies that made the object of research from 31 banking companies. In order to measuring the Good Corporate Governance and Sustainability Disclosures, the author use an index that use on Tember, Bernardus’s (2012) research by eliminating the indicator that less significantly affect the Firm Value and GRI (Global Reporting Initiative) Index with using Linear Regression, F-Test and t-Test.The test result in this study shows that Good Corporate Governance have a significant effect on Firm Value. This shows that the better Good Corporate Governance will increase the Firm Value, otherwise if Good Corporate Governance get worse, it will decrease the Firm Value. Otherwise, Sustainability Disclosure doesn’t have significant effect on Firm Value it caused by the lack of Sustainability disclosure by companies which causes the Firm Value decreases.Keywords: GCG, Sustainability Disclosures, Global Reporting Initiative